A novel compound heterozygous variant in ALPK3 induced hypertrophic cardiomyopathy: a case report - Li, Tiange; Jin, Yuxi; Liu, Rui; Hua, Yimin; Zhou, Kaiyu; Luo, Shuhua; Li, Yifei; Zhang, Donghui (Frontiers in Cardiovascular Medicine, 2023)
Background Malignant hypertrophic cardiomyopathy (HCM) phenotypes have potential risks of severe heart failure, fatal arrhythmia, and sudden cardiac death. Therefore, it is critical to predict the clinical outcomes of these patients. It was reported recently that the alpha kinase 3 (ALPK3) gene was involved in the occurrence of HCM. Herein we reported a girl with HCM, while whole-exome sequencing found novel compound heterozygous variants in ALPK3 gene, which identified a potential association. Case presentation We reported a 14-year-girl who suffered from clinical manifestations of cardiac failure, with sudden cardiac arrest before admission. The heartbeat recovered after cardiopulmonary resuscitation, though she remained unconscious without spontaneous breath. The patient stayed comatose when she was admitted. Physical examination indicated enlargement of the heart boundary. Laboratory results revealed a significant increment of myocardial markers, while imaging demonstrated hypertrophy of the left heart and interventricular septum. Whole-exome sequencing (WES) identified a compound heterozygous variant in ALPK3 gene consisting of c.3907_3922del and c.2200A>T, which was inherited from her parents. Both variants (p.G1303Lfs*28 and p.R734*) were disease-causing evaluated by MutationTaster (probability 1.000). The crystal structure of the complete amino acid sequence is predicted and evaluated by AlphaFold and SWISS-MODEL software (July, 2022), which revealed three domains. Moreover, both variants resulted in a wide protein-truncating variant and damaged protein function. Thus, a novel compound heterozygous variant in ALPK3 associated with HCM was diagnosed. Conclusion We described a young patient with ALPK3-associated HCM who experienced sudden cardiac arrest. Through WES, we identified a compound heterozygous variant in the ALPK3 gene, c.3907_3922del and c.2200A>T, which were inherited from the patient's parents and resulted in a truncated protein, indirectly causing the symptoms of HCM. In addition, WES provided clues in evaluating potential risks of gene variants on fatal clinical outcomes, and the nonsense and frameshift variants of ALPK3 were related to adverse clinical outcomes in HCM patients, which required implantable cardioverter defibrillator (ICD) timely.